The earliest teaching and learning of probability in Singapore, the US, and Indonesia from the perspectives of textbooks analysis. Issue 4 (2nd October 2019) - Yang, Der-Ching; Sianturi, Iwan Andi Jonri
Abstract : This study analyzed how the earliest teaching and learning of probability was organized in Singapore, the US, and Indonesia through an analysis of textbook as an intended mathematics curriculum. An analytical framework was developed comprising four perspectives: representational forms, cognitive demand levels, contextual features, and organization of topics and its uniqueness. This study disclosed that the organization of the earliest teaching and learning of probability in the three countries focused on approximately similar topics, such as basic concepts of probability and probability measurements, although they were intended for different educational levels. Nevertheless, the uniqueness of the organization indicated that students in the three countries may receive different opportunity-to-learn in the earliest teaching and learning of probability in schools. In addition, Singaporean textbook had more exposure to higher-cognitive demand levels and written forms, while the US textbook put more concerns on lower-level demands and visual forms, Indonesian textbook included more proportions of lower- cognitive demand levels and written forms. Moreover, the three textbooks provided considerable opportunity to engage in real-life situations. Considering these results, more studies analyzing other standards-based textbooks and teaching practices might be needed to have further understanding of the organization of probability teaching and learning in schools.